The Deformation Mechanism of the Rings of Angular-Contact Ball Bearings During the Quenching and Tempering Process - Ruijie Gu; Yi Tong; Qiang Wang; Liaoyuan Chen; Ziyang Shang (Machines)
During the heat treatment process, bearing rings are subjected to drastic temperature variability and complex microstructural evolution, which result in deformation, high residual stresses, operational instability and a limited operating life. However, the underlying relationship between temperature, phase transformation, and deformation has not been fully revealed in previous research. As a result, it is difficult to accurately control the roundness of bearing rings during the heat treatment process. Therefore, a combination of numerical simulations and experimental methods was employed to analyze the heat treatment process of the rings of angular-contact ball bearings (ACBB) (7008C). Firstly, according to the multiple coupling theory of thermal, phase-transition, and stress–strain fields, a model for the numerical simulation of the quenching and tempering process was established. Secondly, the thermal–physical properties of the material were calculated using the Jmatpro 7.0 software, and the quenching and tempering processes were numerically simulated using the Deform software. Subsequently, the evolution of the stress, phase-transformation, and deformation behaviors of bearing rings during the quenching and tempering were studied in detail. Finally, the roundness errors of the bearing rings were obtained by a coordinate-measuring machine (CMM). The results showed that the axial and radial stress distributions at the surface and center of the bearing rings were significantly different. The bearing rings experienced uneven expansion and deformation. The roundness errors of the inner diameter and outer diameter of the inner ring were 0.0386 mm and 0.0423 mm, respectively. The roundness errors of the inner diameter and outer diameter of the outer ring were 0.0202 mm and 0.0180 mm, respectively. In this study, the mechanism of the effect of the temperature variation and phase transformation on deformation during the quenching and tempering process was revealed in detail. This provides a reference for controlling the roundness of bearing rings in actual production processes.